Wood shadows: The influence of Xylophaga on hard-substrate macrofauna in Southern California - Ailish Ullmann; Guillermo Mendoza; Michelle Guraieb; Ana Patricia Galindo; Ximena Flores Flores; Lisa A. Levin (PLoS ONE, 2025)
The abundant small taxa on hard substrates in deep-sea environments remain understudied and therefore poorly understood. Abundant seepage, tectonic activity, upwelling, and high productivity generate a diverse array of hard substrates including basalts, carbonate rocks, phosphorites, ferromanganese crusts, and sedimentary rocks throughout the Southern California Borderland (SCB), and wood falls are common given the region’s proximity to land. A comparative experimental approach was used to examine the influence of hard substrate type on patterns of macrofaunal colonization under different environmental conditions, and particularly revealed the outsized influence of the wood-boring bivalve Xylophaga on macrofaunal colonization both on and near wood substrates. The experimental substrates––wood (to assess the influence of organic falls), carbonate rock (to assess faunal affinities for seep-related substrates outside of a seep environment), and other rocks (ferromanganese, phosphorites, and sedimentary rocks, which are common throughout the SCB)––were deployed for ten months at two sites (San Juan Seamount, 40-Mile Bank), each at two water depths (~700 m, ~ 1100 m) in the SCB. The settlement of juvenile Xylophaga on wood and nearby substrates drove overall density trends and contributed to the distinct community composition observed among substrate types. Experimental substrates exhibited significantly higher densities than natural rocks, possibly representing the influence of different substrate or earlier successional stages. Diversity was highest on natural rock substrates and lowest on experimental wood substrates, which also exhibited the lowest evenness due to dominance by wood specialists such as Xylophaga , dorvilleid polychaetes, and the ampharetid polychaete Decemunciger sp. Juvenile Xylophaga were found on both experimental wood substrates and nearby rock substrates, and likely provided other species with food, and on wood, with modified (engineered) habitat. These findings suggest that natural wood falls could have a shadow effect on macrofauna of adjacent hard substrates in this region, which merits future study.